The interplay of family capital and learning engagement: Mediating mechanisms in undergraduates’ intentions to take the postgraduate entrance examination - Chen Xiaoman; Zhou Hongfang (PLoS ONE, 2026)
Background The phenomenon of “postgraduate examination fever” has raised concerns about the factors influencing undergraduates’ decisions to pursue graduate education. By conducting a cross-sectional survey of 1,178 undergraduates from Double First Class and ordinary universities in China, this study examines how family capital and learning engagement jointly affect Chinese undergraduates’ intentions to take the national postgraduate entrance examination under theories of capital and student engagement. Methods This study used a bootstrapped mediation analysis, two stage sampling, convenience sampling, and a binary logistic regression model to investigate the impact of these variables on the intention to pursue graduate education in order to ascertain whether learning engagement mediates the impact of family capital among undergraduates from both Double First Class and ordinary universities in China. Results This study reveals that both family capital and learning engagement were significant predictors of students’ intention to pursue graduate studies (p < 0.01). Learning engagement had a notably stronger effect than family capital in the logistic model, odds ratio for learning engagement = 1.62, and 1.20 for family capital, although both were significant. Moreover, family capital had a significant indirect effect on intention through learning engagement, indicating a partial mediating mechanism. Implication The significance of this study lies in its demonstration that family capital influences postgraduate aspirations indirectly through the enhancement of learning engagement, thereby enriching the explanatory power of educational reproduction theories. Furthermore, it offers practical and policy implications by highlighting that narrowing resource disparities while simultaneously fostering student engagement can effectively promote both educational equity and academic advancement.